PEMANFAATAN KONTEN INSTAGRAM @dukcapilsragen SEBAGAI MEDIA SOUNDING PELAYANAN DALAM MEMPERTAHANKAN BRAND AWARENESS BAGI WARGA SRAGEN - Fachrul Eka Jaya Pratama; Andri Astuti Itasari (Solidaritas, 2025)
This study aims to analyze the use of Instagram content @dukcapilsragen as a service sounding media to maintain brand awareness among Sragen residents. The AISAS theory (Attention, Interest, Search, Action, Share) is used as the analytical framework. This research employed a qualitative method with a case study approach at the Population and Civil Registration Office (Disdukcapil) of Sragen and nearby residents. Data were collected through in-depth interviews with eight informants and validated using source triangulation. The findings show that Instagram functions optimally as a digital service information hub, a medium for service innovation, and an interactive platform between Disdukcapil and the community. Content such as short videos, testimonials, and service documentation demonstrate transparency while building emotional closeness with citizens. The study concludes that Instagram utilization can enhance brand awareness through consistent content, active interaction, and flagship programs such as SEMEDI (Sedino Mesti Dadi).Keywords: Brand Awareness, Disdukcapil Sragen, Instagram, Digital content